Analisis Efektivitas Iklan Restoran Melalui Media Sosial Daring (Online) (Studi Pada Masyarakat Di Tangerang Selatan) - Tito Siswanto; Asriyal Asriyal; Yanti Budiasih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
This research examines the level of advertising effectiveness carried out by restaurants on online Social Media. The research was conducted in South Tangerang City by taking 43 respondents who have online social media and have seen restaurant advertisements online. The objectives of this research are: (1) to determine the relationship between the use of advertising on online social media based on AIDA with consumer responses in making purchasing decisions; (2) to determine the effectiveness of restaurant advertisements on social media based on the EPIC dimension in encouraging consumers to make purchasing decisions. This research is a quantitative study using canonical correlation analysis and EPIC analysis model that is used to answer the research problem. From the results of the data analysis that has been done, it is known that in advertising activities on social media, the duration of advertising in the advertising attribute gives a big contribution compared to other aspects. However, although ad duration is a very important aspect in this research, it is not clear what the ideal ad duration to do. Overall, advertising attributes have a very close relationship with audience response. Furthermore, from the 4 (four) dimensions contained in the AIDA approach, it is known that the dimension of desire has a major contribution to the audience response. The finding can be said that advertising on social media is able to give a desire to viewers to make a purchase. Meanwhile, the results of the analysis using the EPIC model, advertising on social media is considered effective. On each dimension measured, advertising on social media can score well in encouraging viewers to make a purchase. However, there are two dimensions that have a dominant score, namely the empathy dimension and the impact dimension